HISTORY OF SAMARKAND LIBRARY OF THE 19TH CENTURY - Mustafoev Jafar Shomirzoevich; Khanmroeva Leila Nemat kizi (Лучшие интеллектуальные исследования, 2024)
Abstract: This article is devoted to judges and courts operating in the Samarkand region, telling about outstanding judges of the late 19th - early 20th centuries.